Ultra-high adsorption capacity of zeolitic imidazole framework-67 (ZIF-67) for removal of malachite green from water. (November 2015) - Lin, Kun-Yi Andrew; Chang, Hsuan-Ang
Graphical abstract: Highlights: ZIF-67 as the first ZIF for adsorption of Malachite Green (MG) in water is investigated. Kinetics, equilibrium, thermodynamics of the MG adsorption are determined. ZIF-67 exhibits 2430 mg g −1 MG adsorption at 20 °C and ∼3000 mg g −1 at 40 °C. Regeneration efficiency of ZIF-67 for MG is >95% and remains up to 4 cycles. Removal of MG from the aquaculture wastewater using ZIF-67 is demonstrated. Abstract: Zeolitic imidazole frameworks (ZIFs), a new class of adsorbents, are proposed to adsorb Malachite Green (MG) in water. Particularly, ZIF-67 was selected owing to its stability in water and straightforward synthesis. The as-synthesized ZIF-67 was characterized and used to adsorb MG from water. Factors affecting the adsorption capacity were investigated including mixing time, temperature, the presence of salts and pH. The kinetics, adsorption isotherm and thermodynamics of the MG adsorption to ZIF-67 were also studied. The adsorption capacity of ZIF-67 for MG could be as high as 2430 mg g −1 at 20 °C, which could be improved at the higher temperatures. Such an ultra-high adsorption capacity of ZIF-67 was almost 10-times of those of conventional adsorbents, including activated carbons and biopolymers. A mechanism for the high adsorption capacity was proposed and possibly attributed to the π–π stacking interaction between MG and ZIF-67. ZIF-67 also could be conveniently regenerated by washing with ethanol and the regeneration efficiency could remain 95% up to 4 cycles of the regeneration. ZIF-67 was also able to remove MG from the aquaculture wastewater, in which MG can be typically found. These features enable ZIF-67 to be one of the most effective and promising adsorbent to remove MG from water.